Peningkatan Kemampuan Berhitung Melalui Permainan Tradisional Dakon di Raudhatul Athfal Al Kamal 1 Palaran Samarinda - Rinda, Rinda; Robingatin, Robingatin; Saugi, Wildan (Universitas Negeri Padang, 2020)
Along with the development of science and technology, traditional games that can develop children’s skills still exist. One of them is dakon. This research is a classroom research aimed to develop arithmetic skills at Raudhatul Athfal Al Kamal 1 Palaran Samarinda. The research subjects were 12 students with 6 males and 6 females. The traditional game dakon focuses on introducing number 1-20, mentioning the number order 1-20, and sorting numbers of dakon. This research was carried out through two cycles with three meetings each cycle. The result of research shows that before the treatment the students’ skill is 0%. After the treatment, the skill on the cycle 1 is 31% with developing criteria. On the cycle 2, the skill is 77% with well-developed criteria. Thus, it can be concluded that the traditional game dakon can develop the students’ arithmetic skills of Raudhatul Athfal Al Kamal 1 Palaran, Samarinda.